Structure, stability and water permeation of ([D-Leu-L-Lys-(D-Gln-L-Ala)3]) cyclic peptide nanotube: a molecular dynamics study. Issue 3 (11th February 2018) - Maroli, Nikhil; Kolandaivel, Ponmalai
Abstract: The structural stability of 8 × ([D-Leu-L-Lys-(D-Gln-L-Ala)3 ]) cyclic peptide nanotube (CPN) in water and different phospholipid bilayers were explored by 100 ns independent molecular dynamics (MD) simulations. The role of non-bonded interaction energy between the side and main chains of cyclic peptide rings in different membrane environments assessed, wherein the repulsive electrostatic interaction energy between neighbouring cyclic peptide rings was found adequate to break hydrogen bond energy thereby to crumple CPN. Further, the water permeation across the CPN channel was studied in four types of phospholipid bilayers- DMPG (1, 2-Dimyristoyl-sn-glycero-3-phosphorylglycerol), DMPS (1, 2-Dimyristoyl-sn-glycero-3-phosphoserine), POPC (1-Palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine) and POPE (1-Palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine) from MD simulations. DMPS membrane shows higher non-bonded interaction energies (−1913.06 kJ/mol of electrostatic interaction energy and −994.13 kJ/mol of van der Waals interaction energy) with CPN due to the presence of polar molecules in lipid structure. Thusly, the non-bonded interaction energies were essential towards the stability of CPN than hydrogen bonds between the nearby cyclic peptides. The result also reveals the role of side chains, hydrogen bonds and non-bonded interaction energies in an aqueous environment. The diffusion coefficient of water obtained from means square deviation calculation shows similar coefficients irrespective of the lipid surroundings. However, the permeation coefficients demonstrate water flow in the channel relies upon the environment.